The Impact of exposing rural grade 10 mathematics learners to Artificial Intelligence - 1Ndimeni KaNdimeni Olibhisi Majingo; Tirivanhu Muchuweni; Benjamin Tatira (International Journal of Educational Innovation and Research, 2026)
Artificial Intelligence (AI) is transforming classroom learning by providing instant feedback, multiple solution strategies, and opportunities for independent exploration. AI tools such as Photomath can enhance mathematics understanding and engagement, yet many rural schools face significant barriers, including inadequate infrastructure, poor internet connectivity, and limited digital skills. This study explored the impact of introducing Photomath as an AI-based tool to Grade 10 mathematics learners in a rural South African school. Drawing on the Technological Pedagogical Content Knowledge (TPACK) framework, this qualitative study collected data through learner interviews and classroom observations during a six-week intervention. A total of 47 Grade 10 learners participated in the study. Findings revealed increased learner confidence, improved conceptual understanding, and greater willingness to participate in class discussions, as reported by learners and teachers. Learners valued the ability to revisit explanations, explore multiple solution paths, and learn at their own pace. Teachers observed that AI encouraged more focused engagement and active questioning. However, limited access to devices and unreliable connectivity restricted consistent use. The study concludes that, with improved access, teacher training, and infrastructure, AI has strong potential to support inclusive and equitable mathematics education in under-resourced rural contexts, with practical implications for classroom instruction and teacher support in rural schools.